Adaptation of ISPO to The EUDR in Shaping Indonesia's Normative Position in The Global Palm Oil Market - Dini Septyana Rahayu; Def Nakhesfi Ula; Afni Regita Cahyani; Novi Rizka Amalia (Journal of International and Local Studies, 2026)
This study analyzes Indonesia’s normative adaptation through the Indonesian Sustainable Palm Oil (ISPO) framework in response to the European Union Deforestation Regulation (EUDR) and evaluates its implications for Indonesia’s sustainability diplomacy in the global palm oil market. The EUDR, which establishes new standards for deforestation-free commodities, poses significant challenges for Indonesia as the world’s largest palm oil producer because the regulation may restrict access to the European Union market, one of Indonesia’s key trading partners. Although Indonesia has implemented ISPO as its domestic sustainability framework, fundamental differences between ISPO and the EUDR—particularly regarding due diligence mechanisms, cut-off dates, and traceability requirements—raise questions about how Indonesia can respond to global normative pressures without undermining the socio-economic conditions of industry actors, especially smallholder farmers. This research employs a descriptive qualitative method using regulatory documents, official reports, expert interviews, and academic literature as data sources. The analysis applies a constructivist approach through Amitav Acharya’s concept of constitutive localization. The findings indicate that Indonesia responded to the EUDR through a strategy of selective adaptation involving reframing, grafting, and pruning of global sustainability norms. This adaptation is reflected in the strengthening of traceability requirements, the expansion of ISPO certification coverage to the bioenergy sector and downstream industries, and institutional consolidation aimed at enhancing regulatory legitimacy. However, several EUDR provisions considered incompatible with Indonesia’s domestic context—such as the cut-off date and operator-based due diligence model—were not adopted because of their potential to burden smallholders and create structural inequities. The study concludes that ISPO adaptation represents a form of normative localization that repositions Indonesia from a norm taker to a norm shaper, enabling the country to maintain regulatory sovereignty while strengthening its sustainability diplomacy amid increasing global regulatory pressures.